Multicenter prospective cohort study on colorectal adenoma recurrence and malignant transformation risk based on integrative medicine: a study protocol - Hui, Yi-Fan; Song, Shao-Chen; Zhu, Wen-Jian; Bu, Shu; Sun, Jin; Ling, Ting-Sheng; Cheng, Hai-Bo (Frontiers in Oncology, 2025)
IntroductionColorectal adenoma (CRA), the main precursor of colorectal cancer (CRC), has a high recurrence rate (5-year cumulative: 48 - 68%) and a malignant transformation risk (0.2 - 0.5%). Traditional Chinese Medicine (TCM) provides a potential method to improve risk assessment and prevention. Based on TCM theories and the characteristics of colorectal adenoma, we hypothesize that an integrated system combining TCM syndromes, constitution types, and modern medical parameters can better predict adenoma recurrence and CRC occurrence.Methods and analysisThis is a multicenter prospective cohort study. A total of 15,000 patients with colonoscopy-confirmed colorectal adenomas will be recruited from 12 tertiary hospitals in China. At baseline, TCM characteristics (syndromes, constitution, tongue and pulse features), endoscopic findings, and biological samples (tongue coating, saliva, stool, blood, tissue) will be collected. The participants will be followed up for 5 years with risk-stratified standardized colonoscopy intervals. The primary outcomes are adenoma recurrence and CRC occurrence. The secondary outcomes include identifying risk factors and developing a predictive model. Multivariable logistic regression, Cox models, and mixed-effects models will be used for data analysis. A comprehensive biobank will be established to support future mechanistic studies.Ethics and disseminationEthical approval has been obtained from the Institutional Review Board of the Affiliated Hospital of Nanjing University of Chinese Medicine. Written informed consent will be obtained from all participants, who can withdraw at any time without prejudice.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT06136026, identifier NCT06136026.